Evaluasi Penerapan Kebijakan Program Kartu Identitas Anak (KIA) di Kabupaten Padang Pariaman - Wawan Erizona; Lince Magriasti (Journal of Education on Social Science (JESS), 2026)
The Child Identity Card (KIA) Program is a national policy in the field of population administration that aims to provide official identification for children as part of fulfilling civil rights and improving the quality of public services. In Padang Pariaman Regency, the KIA Program has been implemented for the past few years, but KIA ownership is not yet optimal. Problems encountered include low public understanding and awareness of the benefits of KIA, the lack of integration of KIA with other public services such as education and health, and technical obstacles in the document issuance and distribution process. This study aims to evaluate the implementation of the Child Identity Card (KIA) Program in Padang Pariaman Regency by examining policy implementation, policy outcomes, and supporting and inhibiting factors for its implementation by the Population and Civil Registration Office. The study used a qualitative approach with descriptive methods. Data collection was conducted through in-depth interviews, observations, and documentation studies with Disdukcapil (District Population and Civil Registration) officials, village officials, schools, and the community as service recipients. Data analysis was conducted using William N. Dunn's policy evaluation criteria, which include effectiveness, efficiency, adequacy, equity, responsiveness, and feasibility, as well as Pressman and Wildavsky's implementation framework, which includes resource availability, inter-agency coordination, clarity of tasks and procedures, and bureaucratic complexity. The results indicate that the implementation of the KIA Program in Padang Pariaman Regency has been carried out administratively through various service innovations and is relatively efficient. However, effectiveness, adequacy, equity, and feasibility are not optimal due to limited infrastructure, weak cross-sectoral coordination, and low utilization of KIA in public services. Therefore, policy strengthening and cross-sectoral integration are needed so that the benefits of the KIA Program can be felt more evenly and sustainably.